Rapid determination of fructooligosaccharide in solar‑dried banana syrup by using near‑infrared spectroscopy - Udomkun, Patchimaporn; Rungpichayapichet, P.; Phuangcheen, N.; Innawong, B. (Springer, 2021)
The transformation of value-added solar-dried banana to banana syrup, which contains very high levels of fructooligosaccharides (FOS), is attractive. It has promising economic potential for the nutraceutical and functional food industry. In this study, the near-infrared (NIR) spectroscopy was used for the detection of 1-kestose (GF2), nystose (GF3), 1F-fructofuranosylnystose (GF4), and total FOS in solar-dried banana syrup in the spectral region of 4000–12,000 cm−1. Partial Least Squares (PLS) were applied to build the regression models. Considering the highest coefficient of determination (R2) and the lowest root mean square error (RMSE) of prediction, the prediction model of GF2 and GF3 yielded the greatest when original spectra at the optimization wavelength region was used. At the same time, the SNV procedure exhibited the best for the prediction model of GF4 and total FOS. Therefore, NIR spectroscopy with the PLS technique can be suitably applied for the rapid detection of FOS in solar-dried banana syrup.